DARI NORMA KE REALISASI: KRITIK TERHADAP ABSENNYA JAMINAN FISKAL DALAM PEMENUHAN HAK PENYANDANG DISABILITAS PADA PERATURAN DAERAH PROVINSI GORONTALO NOMOR 4 TAHUN 2023 - Mohammad Syafril Rinaldy Hulalata; Zamroni Abdussamad; Mohamad Hidayat Muhtar (LPPM Universitas Doktor Husni Ingratubun Papua, 2026)
This study aims to analyze the implications of the absence of fiscal guarantees on the effectiveness of fulfilling the rights of persons with disabilities under Regional Regulation of Gorontalo Province Number 4 of 2023. The research employs a normative juridical method using statutory, conceptual, and analytical approaches. The rights of persons with disabilities are categorized as social rights whose realization requires active fiscal intervention within the framework of a welfare state. The findings indicate that although the regional regulation has incorporated progressive norms concerning the protection and fulfillment of rights, the provisions on financing remain general and do not contain explicit fiscal guarantee schemes, such as minimum budget allocations or binding affirmative mechanisms. The absence of such fiscal guarantees results in the implementation of rights being highly dependent on the annual regional budgeting policy through the Regional Revenue and Expenditure Budget (APBD), which is political and dynamic in nature. This condition creates the risk of symbolic regulation, weakens legal certainty, and reduces the practical effectiveness of the norms. Therefore, an integration between substantive norms and a structured and sustainable fiscal design is required to ensure that the protection of the rights of persons with disabilities does not remain merely declaratory, but is realized concretely and consistently in accordance with the principles of the welfare state.